A model for pressure driven analysis-design of water distribution networks. Issue 2 (2nd April 2020) - Shirzad, Akbar
Abstract : Pressure Driven Analysis (PDA) method provides the ability to simulate Water Distribution Networks (WDNs) more realistically. Most of the PDA-based models use either the Newton–Raphson method or the gradient method for simulation. The computational cost of these models is high, so that in the solution process of them a large system of equations is solved in each iteration. This paper presents a new model for PDA-based design and analysis of WDNs. The proposed model developed employing the graph portioning approach is named GPDA model. This model provides the PDA-based design and analysis of WDNs without any need of iterative computations for governing equations. Two example networks are designed and analyzed using the proposed model and the results are discussed. The obtained results confirm the ability and computational efficiency of the GPDA model for the design and analysis of WDNs.